STRATEGY SOCIAL MEDIA MARKETING DALAM MEMBANGUN BRAND ENGAGEMENT PADA MEDIA SOSIAL MY BURGER - Yousuf, Gilbert Budiman; Mathory, Eljihad Akbari Syukriah (Politeknik STIA LAN Makassar, 2025)
The development of digital marketing has encouraged business actors to utilize social media as an effective promotional tool, including micro-enterprises such as My Burger. This study aims to analyze how strategies are used to build brand engagement through the distribution of promotional videos on Instagram. The strategy was designed to capture audience attention, convey information visually, and drive engagement with the brand. This research uses a descriptive qualitative approach with data collected through in-depth interviews with five informants who had watched the My Burger promotional video. The data were analyzed based on the three dimensions of brand engagement: cognitive, emotional, and behavioral. The results show that audiences paid attention to the visual elements of the video, understood the promotional message, and became interested in learning more about the product. Emotionally, the video evoked a sense of enjoyment, curiosity, and attraction to the brand. Behaviorally, some informants expressed interest in purchasing, sharing the content, and following My Burger's social media account. These findings indicate that a communicative strategy aligned with audience preferences can effectively build consumer engagement with the brand. This study recommends that micro-businesses optimize their use of social media by producing authentic, lightweight, and visually appealing content to foster long-term relationships with their audience.